Mannose functionalized plain and endosomolytic nanocomposite(s)-based approach for the induction of effective antitumor immune response in C57BL/6 mice melanoma model. (3rd July 2019) - Sharma, Rajeev; Vyas, S. P.
Abstract: The goal of present study to assess the antigen specific immunopotentiation effect of mannose functionalized endosomolytic and conventional nanocomposite(s) based combination approach using C57BL/6 mice melanoma model. Endosomolytic and conventional nanocomposite(s) were prepared by double emulsification method. The optimized formulation was extensively characterized for average particle size, zeta potential and PDI of nanocomposite(s) which were measured in range of ≈200 nm, 0.111 ± 0.024, –23.4 ± 2.0 mV, respectively. pH-dependent morphological changes in the surface of MRPRPNs and PRPNs were analyzed by using surface electron microscopy at different time intervals. The cellular uptake assessment of developed formulations were followed by using RAW 264.7 macrophage cell lines. Results revealed that after immunizing B16F10 melanoma cells implanted C57BL/6 mice with combination [endosomolytic and conventional nanocomposite(s)] of nanocomposite(s), a significant increase in the interleukins level i.e. IL-2, IFN-ϒ, IL-12 and IL-6 and OVA Ag(s) specific antibody responses were recorded. Consequently, a strong immunological response was elicited with specific polarization contributing to humoral and activation of CD8 + to cellular responses. Finding of histological examination also support the potential of therapeutic outcome. The present approach based on mannose surface functionalization for targeting to antigen presenting cells and pH-dependent prompt endosomal release and escape can be a promising system for efficient cancer immunotherapy.